Lampion Games as a Group Guidance Technique to Enhance Cooperation Skills Among Students at Singkawang Elementary School - Iip Istirahayu; Nandang Rusmana; Yusi Riksa Yustiana (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to explore the use of Lampion games as a technique in group guidance to enhance students' cooperation skills at Singkawang Elementary School. The method employed is a qualitative approach with observations and interviews. The results indicate that Lampion games are effective in promoting social interaction, communication, and mutual trust among students.